2008
DOI: 10.1002/ana.21288
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene: Parkinsonism and complex 1 mitochondrial neurotoxicity

Abstract: Trichloroethylene, used extensively in industry and the military and a common environmental contaminant, joins other mitochondrial neurotoxins, MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) and some pesticides, as a risk factor for parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 37 publications
10
148
1
Order By: Relevance
“…2), which is used extensively in industry as a degreasing agent and is a common environmental contaminant, has recently been epidemiologically linked to Parkinson's disease in humans who worked near a TCE source and who were chronically subjected to inhalation and dermal TCE exposure (37). Subsequently, in two different studies conducted in rats, TCE treatment led to selective mitochondrial complex I impairment, selective loss of DA neuron cell bodies in the SN and cell fibers in the striatum, and motor deficit (37,60). In one study, intracellular a-synuclein accumulation was observed in nigral neurons and in the dorsal motor nucleus of the vagus nerve (60).…”
Section: Other Pesticides and Complex I Inhibitors In Parkinson's Dismentioning
confidence: 99%
“…2), which is used extensively in industry as a degreasing agent and is a common environmental contaminant, has recently been epidemiologically linked to Parkinson's disease in humans who worked near a TCE source and who were chronically subjected to inhalation and dermal TCE exposure (37). Subsequently, in two different studies conducted in rats, TCE treatment led to selective mitochondrial complex I impairment, selective loss of DA neuron cell bodies in the SN and cell fibers in the striatum, and motor deficit (37,60). In one study, intracellular a-synuclein accumulation was observed in nigral neurons and in the dorsal motor nucleus of the vagus nerve (60).…”
Section: Other Pesticides and Complex I Inhibitors In Parkinson's Dismentioning
confidence: 99%
“…Add to this the inability to accurately estimate exposure dose -and the likelihood that disease-relevant exposures may have occurred years or even decades before symptom onset -and it is easy to see why so little is known regarding the potential etiologic associations. Recently, Gash et al reported a cluster of three PD patients who had been extensively exposed to the solvent trichloroethylene (TCE) in a small manufacturing plant [26]. The patients had all worked near each other, and had copious dermal and respiratory exposure to TCE for more than 25 years.…”
mentioning
confidence: 99%
“…The patients reported neurological symptoms (headache, dizziness), skin effects, and liver dysfunction [Xu, et al 2009]. Gash et al [2008] reported 3 workers that were exposed to TCE both through chronic inhalation and dermal contact for 25 years or greater had Parkinson's disease (PD). Of these workers, 2 had no family history of PD.…”
Section: Systemic Toxicity From Skin Exposure (Sk: Sys)mentioning
confidence: 99%
“…Of these workers, 2 had no family history of PD. The workers shared the same work hours, including overtime, and cleaned parts directly in a vat of TCE without use of gloves or other protective equipment [Gash et al 2008]. Other workers in the same factory, more distant from the source of TCE who were exposed via inhalation, reported neurological symptoms, such as significant motor slowing [Gash et al 2008].…”
Section: Systemic Toxicity From Skin Exposure (Sk: Sys)mentioning
confidence: 99%
See 1 more Smart Citation